Posted by Aparna on Friday, January 25, 2013 at 9:44pm.
2x - x dy/dx - y + 2y dy/dx = 0
dy/dx(2y - x) = y - 2x
dy/dx = (y-2x)/(2y-x)
B) for a vertical tangent dy/dx is undefined
For that to happen , the denominator has to be zero
2y - x = 0
or x = 2y
sub back into original:
(2y)^2 - (2y)(y) + y^2 = 9
4y^2 - 2y^2 + y^2 = 9
3y^2 = 9
y^2 = 3
y = ± √3
if y =+√3 , then x = 2√3 ---> point (2√3, √3)
if y = -√3 , then x = -2√3 ---> point (-2√3, -√3)
C) at (0,3)
dy/dx = (3 - 0)/(6-0) = 1/2
last calc question, i promise! - given the curve x + xy + 2y^2 = 6... a. find an...
calculus - 1. Given the curve a. Find an expression for the slope of the curve ...
please help; calc - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+...
12th Grade Calculus - 1. a.) Find an equation for the line perpendicular to the ...
Help Calc.! - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+y^2+1...
Ap Calc AB - Find the equation of the line tangent to the curve at (5, -3) (x-2...
Calc - Hi! Please help :-) Find an equation for the circle of the curvature of ...
Calculus ap - Use implicit differentiation to find the slope of the tangent line...
Calculus - Please help this is due tomorrow and I dont know how to Ive missed a ...
Calc - find the slope of the tangent to the curve: y^2=x^3/xy
For Further Reading